Origins of Abrupt Capacity Degradation in Lithium-Ion Batteries with Silicon-Based Anodes - Choi, Yoon Jeong; Bae, Ji-Youn; Park, Seongsoo; Kim, Yeseul; Kim, So Hee; Lee, Hansol; Bae, Jong-Seong; Kim, Taeho; Shin, Sunyoung; Lee, Yongju; Weon, Byung Mook; Moon, Janghyuk; et al. (Wiley-VCH Verlag, 2025)
The incorporation of silicon monoxide (SiO) into graphite anodes improves the energy density of lithium-ion batteries. However, it falls short of the long-term durability of pure graphite, and research on their cycling performance remains limited. This study observes a sudden capacity decay in graphite/SiO anodes during long-term cycling at room temperature (RT) and a moderate C-rate. This decay arises from the mechanical degradation of SiO, leading to the formation of a "SiO-SEI crust" that consumes lithium ions. This phenomenon does not occur at higher temperatures or lower C-rates, implying that larger diffusion-induced stress from lithium-ion gradients at RT and 1 C accelerates SiO degradation. Furthermore, introducing a relaxation step to reduce the lithium-ion gradient mitigates this sudden capacity decay, supporting diffusion-induced stress as a critical factor in the degradation mechanism. These findings emphasize the role of diffusion-induced stress in the performance degradation of Si-based batteries and provide valuable insights for enhancing the lifespan of composite anodes.